Efecto de la variación de los ciclos de luz oscuridad en el perfil lipídico de rattus norvegicus - Sánchez Soto, Manuel Eduardo (2016)
The metabolic process follows a circadian rhythm. Circadian rhythm is influenced by changes in the light/darkness cycles. One of these metabolic processes have to do with lipid synthesis. Lipidic profile quantifies this synthesis. This research was conducted in order to determine the variation of lipidic profile by the variation of light/darkness cycles. Objectives: To determine the effect of light/darkness variation on lipid profile of Rattus norvegicus. Methods: 20 rats (Rattus norvegicus) was used separated in two groups (control and experimental) and housed with variances in light/darkness cycles. Thereafter a blood sample was taken in order to dosage lipid profile (cholesterol, triglycerides, HDL and LDL) before and after variation of light/darkness cycles. Statistical analyses were conducted using Student’s t-test for cholesterol, triglycerides, HDL and LDL Results: Normality of samples was verified in all cases (Shapiro-Wilk Test P-value>0.05). A significative increase was found inside both control and experimental group for levels of triglycerides (p=0.000 y 0.001), HDL (p=0.000 y 0.000) and LDL (p=0.000 y 0.000). And so for cholesterol control group (p=0.015), but in the experimental group difference was not significative (p=0.19). Although this findings, intergroupal comparative analyses for each variable did not show significative differences for none group. Conclusions: 12/12 and 24/0 light/dark cycles significantly increased of triglycerides and HDL levels. These same cycles significantly lowered LDL levels. 12/12 light/dark cycles significantly lowered cholesterol levels, meanwhile 24/0 cycles light/dark had no effect. No intergroup significant differences when comparing changes in these variables were found